2015
DOI: 10.1186/s12960-015-0049-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of physician–nurse task shifting in primary care on the course of disease: a systematic review

Abstract: BackgroundPhysician–nurse task shifting in primary care appeals greatly to health policymakers. It promises to address workforce shortages and demands of high-quality, affordable care in the healthcare systems of many countries. This systematic review was conducted to assess the evidence about physician–nurse task shifting in primary care in relation to the course of disease and nurses’ roles.MethodsWe searched MEDLINE, Embase, The Cochrane Library and CINAHL, up to August 2012, and the reference list of inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 41 publications
(59 reference statements)
2
60
0
6
Order By: Relevance
“…Task shifting can produce equivalent or superior outcomes for many diseases and health interventions including non-communicable diseases [5], HIV/AIDS [6, 7], contraceptive distribution [8], and others [5, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Task shifting can produce equivalent or superior outcomes for many diseases and health interventions including non-communicable diseases [5], HIV/AIDS [6, 7], contraceptive distribution [8], and others [5, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…One solution for this shortage of providers has been the development and increased utilization of nonphysician PCPs such as advanced practice registered nurses (APRNs; Maier, 2015;Pulcini, Jelic, Gul, & Yuen, 2010;Sheer & Wong, 2008). Evidence demonstrates that APRNs who practice as independent care providers are producing similar patient outcomes to primary care physicians (Fund & Swanson-Hill, 2014;Horrocks, Anderson, & Salisbury, 2002;Laurant et al, 2009;Martinez-Gonzalez, Tandjung, Djalali, & Roseman, 2015;Newhouse et al, 2011). Consequently, researchers and policymakers alike have been advocating for the expanded practice and autonomy of APRNs to assume an enhanced role in health care.…”
Section: Introductionmentioning
confidence: 99%
“…• This paper deepens our understanding of traditional role concepts legal frameworks and reimbursement schemes as limiting barriers to a more integrated interprofessional collaboration which is required by current and future challenges in primary health care workload, decreases healthcare costs, improves satisfaction of both patient and healthcare provider (HCP) and provides equivalent or improved quality of care (Gielen, Dekker, Francke, Mistiaen, & Kroezen, 2014;Laurant et al, 2018;Martínez-González et al, 2014;Martínez-González, Tandjung, Djalali, & Rosemann, 2015;Parker, Maresco-Pennisi, Clifton, Shams, & Young, 2016;Riisgaard, Nexoe, Le, Sondergaard, & Ledderer, 2016;Watts & Lucatorto, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…Nevertheless, a better understanding of the potential contribution of nurses working in general practice is needed (Ball, Maben, & Griffiths, ). Research has demonstrated that this task shift generates similar or better health outcomes for a broad range of patient conditions, relieves the GP’s workload, decreases healthcare costs, improves satisfaction of both patient and healthcare provider (HCP) and provides equivalent or improved quality of care (Gielen, Dekker, Francke, Mistiaen, & Kroezen, ; Laurant et al, ; Martínez‐González et al, ; Martínez‐González, Tandjung, Djalali, & Rosemann, ; Parker, Maresco‐Pennisi, Clifton, Shams, & Young, ; Riisgaard, Nexoe, Le, Sondergaard, & Ledderer, ; Watts & Lucatorto, ). A recent overview of systematic reviews by Matthys Remmen, & Van Bogaert, () demonstrated that collaboration between physicians and nurses may have a positive impact on a range of patient outcomes and on a variety of pathologies when embedded within integrated interprofessional collaboration care models with adequately educated nurses (Matthys et al, ).…”
Section: Introductionmentioning
confidence: 99%